Knowledge Management Process for Product Development from Thai Song-Dum Culture to Utilization and Sustainable Community - Ngamsakoo, Rujirapha; Kruamek, Soracha; Kulprasutidilok, Akua; et al. (Journal of Cultural Approach, 2025)
This research utilized the knowledge management process to develop and design packaging products, using the unique dress of the Thai Song Dam people for inhalants and balm doll products containing Zanthoxylun Limonella or Ma-Kwaen. This research objective aimed to 1) design and develop Thai Song Dam doll packaging products, 2) evaluate consumers’ opinions of the products, and 3) convey the production process of the packaging products. This study used a mixed research method. The sample groups were divided into three groups: 13 key informants were selected using purposive sampling; 407 consumers and general people who were interested in packaging products were selected using convenience sampling; and 102 people involved in conveying the production process of Thai Song Dam doll packaging products volunteered. The results of this research were as follows: 1) It was found that there were ten styles of Thai Song Dam doll packaging products; 2) Consumers’ opinions of Thai Song Dam doll packaging products were at a high level; 3) The production process of Thai Song Dam packaging products was conveyed to a team of 10 assistant lecturers and 92 people and students in Ban Don Subdistrict, U-Thong District, Suphan Buri Province, and the community; 4) The professional group of Ban Don Thai Song Dam Doll was established; and 5) There was a patent on Thai Song Dam doll packaging design.